The Effectiveness of the Think Pair Share (TPS) Model for Increasing Students Mathematical Problem-Solving Ability - Hamzah, Tiara Aprilia Fauzianti; Jasem Al-Tammar (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2023)
Mathematics problem-solving ability is a basic need for students to solve math problems. This study aims to investigate the effectiveness of Think Pair Share (TPS) in increasing Students’ problem-solving abilities. This study uses a qualitative approach with a library research type. The data collection technique is a documentation study, with the data analysis using inductive and interpretative techniques. The analysis result shows that TPS effectively used in teaching. This can be seen from the N-gain test result that shows the increase of the mathematics problem-solving ability at the high level, The learning outcomes data find three studies that reach the complete outcomes. On the other hand, effect size data shows it reaches the medium until the high level. Furthermore, the impact of TPS on student’s learning outcomes is low level, in against to other factors.